2002
DOI: 10.1128/aac.46.12.3877-3882.2002
|View full text |Cite
|
Sign up to set email alerts
|

Coadministration of Indinavir and Nelfinavir in Human Immunodeficiency Virus Type 1-Infected Adults: Safety, Pharmacokinetics, and Antiretroviral Activity

Abstract: Combinations of protease inhibitors (PIs) can have potentially beneficial pharmacokinetic interactions, resulting in higher drug levels and less frequent dose administration. Indinavir (IDV) and nelfinavir (NFV) are potent inhibitors of human immunodeficiency virus type 1 (HIV-1) protease and are commonly prescribed antiretroviral agents. Pilot pharmacokinetic data suggested a bidirectional enhancing interaction between IDV and NFV. A phase II study was conducted to evaluate the safety, pharmacokinetics, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
(9 reference statements)
0
6
0
Order By: Relevance
“…2) and higher 24-h AUCs. This interaction was not evident in the only other report of this combination (12). For example, Fig.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…2) and higher 24-h AUCs. This interaction was not evident in the only other report of this combination (12). For example, Fig.…”
Section: Discussionmentioning
confidence: 79%
“…Subsequently, a small study demonstrated the antiviral effect of indinavir-nelfinavir combinations, with 45% of subjects achieving Ͻ400 viral copies/ml at week 72 (12). Interestingly, the pharmacokinetic profiles in the subjects we studied suggest that some type of interaction is at work when indinavir and nelfinavir are taken together.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many drugs used in the treatment of HIV (nucleosides, nonnucleosides, and protease inhibitors) include diarrhea among their documented side effects. This side effect has been well documented in regimens that include protease inhibitors (PIs) (15)(16)(17)(18). Studies have shown that saquinavir, ritonavir, and nelfinavir impair the epithelial barrier in the human intestinal cell line HT-29/B6 as one mechanism of action for diarrhea (19).…”
mentioning
confidence: 98%